2015
DOI: 10.5312/wjo.v6.i11.902
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tears: An evidence based approach

Abstract: Lesions of the rotator cuff (RC) are a common occurrence affecting millions of people across all parts of the globe. RC tears are also rampantly prevalent with an age-dependent increase in numbers. Other associated factors include a history of trauma, limb dominance, contralateral shoulder, smoking-status, hypercholesterolemia, posture and occupational dispositions. The challenge lies in early diagnosis since a high proportion of patients are asymptomatic. Pain and decreasing shoulder power and function should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(166 citation statements)
references
References 176 publications
0
158
0
8
Order By: Relevance
“…Rotator cuff tendinopathy is one of the most common musculoskeletal conditions and the most common shoulder pathology, affecting 15% to 50% of the population and increasing in prevalence with age . It is a unique challenge for physicians as it presents with a wide range of pathologies, which only loosely correlate to symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Rotator cuff tendinopathy is one of the most common musculoskeletal conditions and the most common shoulder pathology, affecting 15% to 50% of the population and increasing in prevalence with age . It is a unique challenge for physicians as it presents with a wide range of pathologies, which only loosely correlate to symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…RCT treatment responses are poor, as non-operative management fails in approximately 50% of patients, leaving surgical tendon repair as the standard of care [4], [5]. The failure rate of surgery is as high as 26% for small to medium tears and up to 94% for large and massive tears[32]–[37].…”
Section: Discussionmentioning
confidence: 99%
“…Non-operative treatment has been recommended as an initial treatment for patients with rotator cuff pathology ranging from tendinopathy to partial and even complete RCTs [80]. Although several reviews and studies have demonstrated the effectiveness of non-operative treatment in RCTs, as previously described, there are concerns regarding the risks of conservative treatment as well.…”
Section: Risks Of Conservative Treatment In Managing a Rotator Cuff Tearmentioning
confidence: 96%